Final year project (FYP) presentation timetable - Nur Asmira, Md Nor (2018)
Final Year Project Presentation Time Table is a web based for UMP resident who are involve on Final Year Project. The purpose of this system have been developed is for PSM students, PSM supervisor, PSM coordinator and PSM examiner easily access their presentation time table for evaluation day. Before this system have being develop, the PSM coordinator required to assign the examiner for the each student and supervisor. The processes of the presentation time table have being done manually using Microsoft Excel. This system being develop is to enhance the current process of presentation time table. This system is providing the student, supervisor and examiner to view the time table. This system will help the coordinator in managing the presentation time table for student and lecturer.